The WASp L272P gain‐of‐function mutation alters dendritic cell coordination of actin dynamics for migration and adhesion. Issue 4 (25th August 2021) - Oliveira, Mariana M.S.; Kung, Shin‐Yu; Moreau, Hélène D.; Maurin, Mathieu; Record, Julien; Sanséau, Doriane; Nylén, Susanne; Lennon‐Duménil, Ana‐Maria; Westerberg, Lisa S.
Abstract: Dendritic cells (DCs) devoid of the actin regulator Wiskott‐Aldrich syndrome protein (WASp) show reduced directed migration and decreased formation of podosome adhesion structures. We examined DCs expressing a gain‐of‐function mutation in WASp, WASp L272P, identified in X‐linked neutropenia patients. Analysis of WASp L272P DCs was compared to WASp‐deficient DCs to examine how WASp activity influences DC migratory responses. In confined space, WASp‐deficient DCs had increased migration speed whereas WASp L272P DCs had similar average speed but increased speed fluctuations, reduced displacement, and atypical rounded morphology, compared to wild‐type (WT) DCs. Using an ear inflammation model and flow cytometry analysis, WT, WASp‐deficient, and WASp L272P DCs were found to migrate in comparable numbers to the draining lymph nodes (LNs). However, histology analysis revealed that migratory DCs of WASp deficient and WASp L272P mice were mainly located in the collagenous capsule of the LN whereas WT DCs were located inside the LN. Analysis of ultrastructural features revealed that WASp L272P DCs had reduced cell area but formed larger podosome structures when compared to WT DCs. Together, our data suggest that WASp activity regulates DC migration and that loss‐of‐function and gain‐of‐function in WASp activity lead to different and phenotype‐specific DC migratory behavior. Graphical Abstract: WASp activity regulates dendritic cell (DC) migration; DCs have a remarkable adaptation for migration under inflammatory conditions in vivo.